Local field enhancement at the core of cylindrical nanoinclusions embedded in a linear dielectric host matrix - Abbo, Y.A.; Mal'nev, V.N.; Ismail, A.A. (Condensed Matter Physics, 2016)
In this paper we have discussed theoretical concepts and presented numerical results of local field enhancement at the core of different assemblages of metal/dielectric cylindrical nanoinclusions embedded in a linear
dielectric host matrix. The obtained results show that for a composite with metal coated inclusions there exist
two peak values of the enhancement factor at two different resonant frequencies. The existence of the second
maxima becomes more important for a larger volume fraction of the metal part of the inclusion. For dielectric
coated metal core inclusions and pure metal inclusions there is only one resonant frequency and one peak
value of the enhancement factor. The enhancement of an electromagnetic wave is promising for the existence
of nonlinear optical phenomena such as optical bistability which is important in optical communication and in
optical computing such as optical switch and memory elements. В цiй статтi ми обговорили теоретичнi концепцiї, а також представили числовi результати пiдсилення
локального поля для рiзних компонувань цилiндричних нановключень метал/дiелектрик, вбудованих у
лiнiйну дiелектричну базисну матрицю. Отриманi результати показують, що для композиту з пометалованими включеннями iснує два пiкових значення коефiцiєнта пiдсилення при двох рiзних резонансних
частотах. Iснування другого максимума стає важливiшим для бiльшої об’ємної частки металiчної частини включення. Для металевих включень з дiелектричним покриттям є тiльки одна резонансна частота
i одне пiкове значення коефiцiєнта пiдсилення. Пiдсилення електромагнiтної хвилi є обнадiйливим для
iснування нелiнiйного оптичного явища такого як бiстабiльнiсть, яке є важливим для оптичного зв’язку i
оптичних розрахункiв (оптичнi комутатори i елементи пам’ятi)